2015
DOI: 10.1557/jmr.2015.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloy substituents on soft magnetic properties and economics of Fe-based and Co-based alloys

Abstract: Amorphous and nanocrystalline soft magnetic alloys have garnered interests in academia and industry due to their potentials for applications, such as power transformers, electric motors, and sensors. To achieve good glass formability, thermal stability, and prevent grain overgrowth, elements such as B, Nb, Ta, and Hf are used in many soft magnetic systems. However, the high price of these precursors results in expensive soft magnetic alloys. Herein, we report on substituting Ta and Hf with TaC and HfC, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Increasingly, issues of materials criticality and economics 54 are important in materials choices for applications. Co is not currently on recent materials criticality lists, but it has been in the past and its potential criticality and cost 55 should be considered in component designs. In the benchmarks presented herein, the Fe-Ni-based MANCs compare favorably with Co-based MANCs on a cost per weight basis.…”
Section: Cost Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, issues of materials criticality and economics 54 are important in materials choices for applications. Co is not currently on recent materials criticality lists, but it has been in the past and its potential criticality and cost 55 should be considered in component designs. In the benchmarks presented herein, the Fe-Ni-based MANCs compare favorably with Co-based MANCs on a cost per weight basis.…”
Section: Cost Comparisonsmentioning
confidence: 99%
“…Kurniawan et al 55 and Aronhime et al 18 have reported the individual prices of the precursors used in the synthesis of their compositions. Among the late transition metals, Co is the most expensive at $60/kg, while Fe is the least expensive at only $0.39/kg.…”
Section: Cost Comparisonsmentioning
confidence: 99%
“…In a number of studies, Nb was substituted by other elements such as V, Cr, Mo, etc. . In the literature , Silveyra et al studied Fe 73.5 Si 13.5 B 9 Nb 3− x Mo x Cu 1 ( x = 1.5, 2, at.%) alloys annealed at a fixed temperature and time by Mossbauer spectrum method.…”
Section: Introductionmentioning
confidence: 99%